Pengaruh Model Pembelajaran Auditory, Intellectually, Repetition (AIR) Terhadap Prestasi Belajar Siswa Kelas X Pada Mata Pelajaran Fiqih Di MAS Al-Washliyah Pangkalan Brandan - Elfira, Muhammad Saleh, Diani Syahfitri (Pusdikra Publishing, 2023)
This study focuses on the discussion of the effect of the auditory, intellectually, repetition (AIR) learning model on the learning achievement of class X students in the subject of fiqh at MAS Al-Washliyah Pangkalan Brandan. In this study the authors used a type of quantitative research that is associative. The number of research respondents was 38 students who were in the religion class. Data processing using Microsoft Office Excel and SPSS applications. The results of the study explain that there is a significant influence between the effect of the Auditory, Intellectually, Repetition (AIR) learning model on the learning achievement of class X students in the subject of jurisprudence at MAS Al-Washliyah Pangkalan Brandan. This is obtained through the results of hypothesis testing, namely tests that show a significance value of less than 0.05 (0.000 <0.05) and tcount > ttable (4.499 > 2.02809) so that there is an effect of variable X on variable Y. Auditory learning model , Intellectually, repetition applied by the teacher affects the learning achievement of class X students in fiqh subjects at MAS Al-Washliyah Pangkalan Brandan by 34.2% while the rest is influenced by other variables such as intelligence, interest, talent, motivation, environment, and etc. There is a positive or parallel relationship between the Auditory, Intellectually, Repetition (AIR) learning model and student achievement, the better the application of the Auditory, Intellectually, Repetition (AIR) learning model is carried out, the learning achievement of class X students in fiqh subjects at MAS Al- Washliyah Pangkalan Brandan will get better too, and vice versa if the application of the Auditory, Intellectually, Repetition (AIR) learning model is not good or bad, the learning achievement of class X students in fiqh subjects at MAS Al-Washliyah Pangkalan Brandan will decrease.